Auto-Scaling Variable Step Size Incremental Conductance Maximum Power Tracking Control Algorithm for Photovoltaic System - Hasliza Abdul Rahman, Noor; Iqtiyani Ilham, Nur; Maliki Omar, Ahmad; Hisham Mat Saat, Ezril; Zhafran Hussin, Mohamad; Mohd Hussain, Mashitah; Othman, Norhalida (International Journal of Engineering and Technology, 2018)
Generally, most of the Maximum Power Point Tracking (MPPT) techniques are based on the fixed step size considering to its simplicity and easy execution. However, the fixed step size contributes to the high power oscillation around maximum power point for large step size and slow time response for small step size. In order to compromise between these two problems, the variable step size (VSS) method is proposed. Yet, there are some deficiency occurred in the conventional VSS between time response and power oscillation. Thus, in this research paper, Auto-Scaling Variable Step Size (AVSS) Incremental Conductance (INC) algorithm technique will be employed to improve the trade-off between time response and power oscillation.Â Â